The ketogenic diet alleviates autoimmune thyroiditis caused by Th17/Treg imbalance by inhibiting the HMGB1/NLRP3 signaling pathway - Yue Luo; Hao Gao; Mengzhen Wang; Zhimin Wang; Zhe Jin; Nan Song; Ziyu Liu; Xiao Yang (PLoS ONE, 2026)
Background Autoimmune thyroiditis (AIT), caused by immune-mediated thyroid dysfunction, lacks effective dietary interventions. This study investigates the therapeutic potential of a ketogenic diet (KD) in a murine model of iodine-induced AIT. Methods Sixty 8-week-old NOD.H-2 h4 mice were randomized into three groups: wild-type mice on a normal diet (WT + ND), AIT model mice on a normal diet (AIT + ND), and AIT model mice on a KD (AIT + KD). AIT was induced in model groups via 0.05% sodium iodide administration for 8 weeks, followed by 4 weeks of KD intervention in the AIT + KD group. Outcomes included histopathological thyroid changes, serum levels of TgAb/TPOAb, proinflammatory cytokines (MCP-1, TNF-α, IL-1β, IL-6, IL-18, IFN-γ), oxidative stress markers (MDA, SOD, T-AOC), gene expression of NLRP3 inflammasome components (NLRP3, ASC, Caspase-1), Th17/Treg-related factors (RORγt, IL-17, FoxP3, IL-10), and immune mediators (TLR2/4, NF-κB, HMGB1). Results Compared to the WT + ND group, the AIT + ND group exhibited increased TgAb/TPOAb levels, enhanced thyroid lymphocytic infiltration, elevated proinflammatory cytokines, and aggravated oxidative stress. Concurrently, this group showed upregulated NLRP3 inflammasome activity, promoted Th17 polarization, activated HMGB1/TLR2/4/NF-κB signaling, and a higher Th17/Treg ratio. Ketogenic diet (KD) intervention reversed all these alterations, effectively suppressing inflammation, oxidative stress, and pathogenic immune pathways. Conclusion KD ameliorates iodine-induced AIT in mice by modulating HMGB1/NLRP3-mediated inflammation, restoring immune balance, and reducing thyroid autoimmunity. These findings support KD as a potential adjuvant therapy for AIT, warranting clinical evaluation.